Pengaruh Parenting Skill Terhadap Keterampilan Interaksi Sosial dan Emosional Anak di Sekolah Dasar - Windy Rachmawaty; Siti Bahiroh (Institut Agama Islam Daruttaqwa Gresik, 2025)
In today's digital era, children are faced with new challenges in social interaction, such as the influence of social media, because social media can affect a person's social-emotional life, especially if it occurs in elementary school children. Parenting skills play a very important role in the social and emotional development that children will have. This study aims to determine whether there is an influence between parenting skills on social interaction skills and the influence between parenting skills on children's emotional skills at SDIT Insan Utama Yogyakarta. This study used a quantitative approach with a research sample of 67 students. The results of the study were obtained using the F test and t test which showed that, 1) parenting skills (X) had a significant and positive effect on social interaction skills (Y1) at SDIT Insan Utama Yogyakarta, 2) parenting skills (X) had a significant and positive effect on emotional skills (Y2) at SDIT Insan Utama Yogyakarta. In the determinant coefficient test, the effect produced by the independent variables consisting of parenting skills on social and emotional skills is 29.9%, while 70.1% is influenced by other variables not included in this study.